Research on Urban Green Rainwater and Flood Infrastructure System - Qiang Hu (Forest Chemicals Review, 1970)
Small and medium-sized cities in low latitudes account for a large proportion of the world, which is characterized by rainy weather and a population of less than 2 million. Such small and medium-sized cities are vulnerable to rain and floods. Taking this as the research object, this paper analyzes the development development of rainwater management and expounds the latest technology of new rainwater and flood management. Based on the in-depth analysis of the formation mechanism and characteristics of water-logging in small cities, this paper puts forward the construction plan of urban green rainwater and flood infrastructure system, which puts forward the construction of infiltration, collection GSI planning and design strategy of rainwater comprehensive utilization mode in multi-functional community with integrated discharge function. Practice has proved that the urban green rain and flood infrastructure system can achieve good results in the field of rain and flood control.